EFFORTS TO IMPROVE WRITING SKILLS AND RECOGNIZE EARLY CHILDHOOD NUMBERS AT AISYIYAH BUSTANUL ATHFAL IV - Syifa Pasaribu, Layyinatu (Proceeding International Seminar of Islamic Studies, 2022)
Writing skills are important to be trained from an early age. In terms of writing training, there are several important things that need to be considered, such as children's development and age, fun training for children, and others. The importance of practicing writing skills pays attention to the quality of children's writing related to the importance of writing skills. When assessing a child's writing ability, you can use the level of normal developmental abilities of the child, especially those aged 4-5 years. This criterion is used to monitor the writing skills of early childhood. There are 3 metrics, namely: wearing symbols, creating meaningful doodles, and imitating writing styles. This study aims to describe the application of writing and number recognition skills in Aisyiyah Bustanul Athfal IV Kindergarten. The research subjects used early childhood or group A, school principals, and teachers. Data collection techniques using the method of observation, interviews, and documentation. The results of this study indicate that the skills of writing and recognizing numbers in TK Aisyiyah Bustanul Athfal IV have been implemented well, meaning that children's skills are developing very well. However, there is hope to maximize children's writing skills.